Race and Ethnicity in Real-World Data Sources: Considerations for Medical Device Regulatory Efforts - Michelle E. Tarver MD, PhD (SAGE Publishing, 2021)
Real-world evidence is increasingly being collected in our interconnected world. This information can provide insights on how medical products are impacting the daily lives of patients, translating into public health consequences. Understanding the demographic characteristics of patients contributing health information to real-world data sources is critical to determining the safety and effectiveness of medical products for specific populations. Race and ethnicity are recorded inconsistently in different real-world data sources, with many lacking reliable information on these variables. To better leverage all forms of real-world data to inform medical device evaluation, accurate and consistent collection of information from different racial and ethnic subgroups is necessary.